The emerging female citizen : gender and enlightenment in Spain - Smith, Theresa Ann, 1971- (University of California Press, 2006)
In analysing the meaning of women's presence in these diverse centres of the Enlightenment, Smith offers a new interpretation of the dynamic relationships among political discourse, social action, and gender ideologies.
Keywords: Women -- Spain -- History -- 18th century.; Sex role -- Spain -- History -- 18th century.; Women -- Spain -- Intellectual life.; Women -- Spain -- Social conditions.; Feminism -- Spain -- History -- 18th century.; Femmes -- Espagne -- Histoire -- 18e siècle.; Rôle selon le sexe -- Espagne -- Histoire -- 18e siècle.; Femmes -- Espagne -- Vie intellectuelle.; Femmes -- Espagne -- Conditions sociales.; Féminisme -- Espagne -- Histoire -- 18e siècle.; HISTORY -- Europe -- General.; SOCIAL SCIENCE -- Discrimination & Race Relations.; SOCIAL SCIENCE -- Minority Studies.; Feminism; Sex role; Women; Women -- Intellectual life; Women -- Social conditions; Spain; 1700-1799; History